PATIENT SAFETY IN THE SURGICAL CENTER: ASPECTS IN HEALTH TECHNOLOGIES - Rodrigues Vieira, Edineia; Gomes Viana, Amanda; Barros de Valmoré Fernandes, Marcelo; Conceição de Assis, Jefferson; Carolina Salustino dos Santos, Maria (Health and Society, 2023)
Patient safety in the SC ranges from: keeping the bed’s large bed elevated, infusing the heated serum, turning off the air conditioning in the post-anesthesia recovery room to the use of robotics in surgeries. We cannot forget the use of POPs (standard operating procedure) to standardize and avoid errors in the execution of activities. Technological and digital advances in surgeries have had a positive impact on the health of all of us. With the emergence of COVID-19, the Surgical Center invested a lot in its modernization, such as the use of digital medical records and digital anesthetic chart, with that less paper circulating and carrying infection from one sector to another.